2010
DOI: 10.1016/j.biomaterials.2010.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in gene expression of human vascular endothelial cells associated with nanotopographic cues

Abstract: Human cells in vivo are exposed to a topographically rich, 3-dimenisional environment which provides extracellular cues initiating a cascade of biochemical signals resulting in changes in cell behavior. One primary focus of our group is the development of biomimetic substrates with anisotropic nanoscale topography to elucidate the mechanisms by which physical surface cues are translated into biochemical signals. To investigate changes in gene expression as a result of nanotopographic cues, Human Umbilical Vein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
56
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…This has lead to nanoscale engineering to influence cellular orientation, growth, attachment and migration [32,33] In vitro endothelialisation not only requires adequate cellular attachment, but also rapid proliferation. Slow proliferation increases incubation times leading to higher rates of contamination and production costs.…”
Section: Discussionmentioning
confidence: 99%
“…This has lead to nanoscale engineering to influence cellular orientation, growth, attachment and migration [32,33] In vitro endothelialisation not only requires adequate cellular attachment, but also rapid proliferation. Slow proliferation increases incubation times leading to higher rates of contamination and production costs.…”
Section: Discussionmentioning
confidence: 99%
“…A previously performed gene chip analysis showed no differences in FAK expression between HUVECs cultured on the 400-nm pitch and those cultured on planar surfaces (14). To analyze additional pitch sizes, we performed a qPCR using RNA isolated from HUVECs cultured on topographically patterned surfaces and planar control substrates.…”
Section: Topography Does Not Modulate Inherent Fak Expressionmentioning
confidence: 99%
“…55 An earlier study from our group using human umbilical vein endothelial cells demonstrated that over 3000 genes, many associated with the ECM and cell adhesion, cytoskeletal reorganization, DNA replication and repair, and spindle organization, were significantly altered by biomimetic size scale (400-nm pitch) topographic features. 56 It is known that while nanoscale topographic cues can modulate the expression of integrins in cells, 57 there is bidirectional signaling between the cytoskeleton and integrins. 58 Additionally, the mechanical link between integrins and various cytoskeletal Tracks of fibronectin (yellow trace lines) were followed for cells migrating on FNCcoated topographies.…”
Section: Figmentioning
confidence: 99%